Fiscal covenant strengths, weaknesses, challenges (ECLAC SantiagoCL, 1998)
Summarizes the strengths, weakness and challenges presented by the new fiscal covenant. Analyses the fiscal and quasi-fiscal aspects of public action. Reviews progress and changes in the areas of public-sector revenue, expenditure, deficit and debt. Considers what has been achieved and what remains to be done in key areas of public management with major fiscal implications.
Bibliography: p. 277-292